Growth fitness of indigenous wine yeasts in grape musts from different vitis species - Raymond Eder, María Laura (2021)
Yeast communities associated with Vitis vinifera L. niches (i.e. grapes and fermenting grape musts) have been widely characterized. Less is known, however, about yeast communities present in other non-vinifera Vitis ecosystems. Moreover, there are no studies concerning eventual must-specific growth fitness of indigenous wine yeast species. In this work, we have characterized the potentialmust-specific growth fitness of ten different indigenous wine yeast species (i.e. C. azymoides, C. californica, H. uvarum, H. vineae, I. hanoiensis, M. pulcherrima, P. cecembensis, T. delbrueckii, S. bacillaris and S. cerevisiae). All the analyzed strains were isolated from spontaneously fermenting musts of V. vinifera L. (cv. Malbec) and/or V. labrusca L. (cv. Isabella) grapes harvested from vineyards in a shared terroir. Yeast identification was performed using standard ITS-rDNA RFLPs and/or microsatellite genotyping. Growth fitness of selected yeast species and strains, on Malbec and Isabella pasteurized grape must media, was studied by measuring lag phases (i.e. Lag Time) and maximum growth rates (i.e. µmax). Results showed that rare yeast species isolated from the Isabella ecosystem (i.e. P. cecembensis and I. hanoiensis) have better growth parameters when growing in Isabella grape must. The growth parameters of other wine yeast species, isolated from Malbec and Isabella ecosystems, did not show any clear associations with their musts of origin. Our findings suggest that the presence of two rare yeast species in Isabella could result from their growth advantage to this Vitis ecosystem. It is possible that yeast communities assembled in alternative grape musts result from the growth fitness of yeast species and strains to each specific Vitis species. Non-conventional Vitis ecosystems may constitute a reservoir of unique yeast strains valuable in the winemaking industry